2002
DOI: 10.1080/003655902317259382
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Transurethral Resection of Recurrent Superficial Bladder Tumors: Does it Affect the Spread and Stage of the Tumor?

Abstract: We conclude that some malignant cells penetrate through the denuded urothelium during TURT by the effect of high intravesical pressure. This may be responsible, among other factors, for tumor recurrence with deeper stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…[11][12][13][14][15] The presumed pathways for this dissemination are extravasation of the irrigation fluids by way of blood or lymphatic circulation and=or implantation of tumor cells at the traumatized sites because of the high intravesical pressures generated during transurethral resection. 6,7,16,17 A greater number of recurrences have been shown to develop on the posterosuperior wall, which is probably the most frequent site to be traumatized during TURBT. 10 It has been observed that bladder perforations cause a slight increase in the recurrence rates even for low-grade tumors.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[11][12][13][14][15] The presumed pathways for this dissemination are extravasation of the irrigation fluids by way of blood or lymphatic circulation and=or implantation of tumor cells at the traumatized sites because of the high intravesical pressures generated during transurethral resection. 6,7,16,17 A greater number of recurrences have been shown to develop on the posterosuperior wall, which is probably the most frequent site to be traumatized during TURBT. 10 It has been observed that bladder perforations cause a slight increase in the recurrence rates even for low-grade tumors.…”
Section: Discussionmentioning
confidence: 98%
“…[2][3][4][5] This hypothesis, however, could not be verified in several comparative studies, and the safety issue regarding transurethral resection of superficial TCC of the urinary bladder and transurethral resection of the prostate (TURP) performed in the same sitting remains controversial. [6][7][8][9] Many urologists avoid performing transurethral resection of bladder tumor (TURBT) and TURP in the same sitting because of this lack of information, with the belief that there might be implantation of tumor cells in the prostatic fossa. They, therefore, prefer to undertake separate procedures for each of these pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence to support this theory is based on the histological findings of multifocal malignant cell clusters in the bladder of multi-TURB patients [9] . These theoretical hypotheses are difficult to prove.…”
Section: Discussionmentioning
confidence: 99%
“…El-Abbady et al [11] demonstrated unusual patterns of tumour expansion in cystectomy specimens after previous transurethral resections. When transurethral resection had been performed, bladder tissues showed clusters of malignant cells in between muscle fi bres and perivesical fat.…”
Section: Discussionmentioning
confidence: 99%